Pneumocystis Pneumonia in Covid-19 Outbreak :A Case Report It's not all about Covid-19 - Julisman Hasiholan Situmorang; Ginanjar Arum Desianti (Indonesian Society of Respirology (ISR), 2021)
One of the phenomena during the current Covid-19 pandemic is Early Detection of In-Patient Deterioration by public health services, especially general hospitals for early detection patients who admit with respiratory tract infections (RTIs) symptoms. However, there is a risk of misdiagnosis in differential diagnoses. Pneumocytis Carinii Pneumonia (PCP) is an opportunistic infection that can occur in immunocompromised patients. Symptoms that often appear are similar to Covid-19, such as fever, cough, runny nose, dyspnoea, diarrhea or others. It makes some difficulties for early diagnosing PCP infection during Covid-19 pandemic, whereas if it is not early treated it is could be a fatal case. Thus, during Covid-19 pandemic, it is necessary to consider other differential diagnoses in patients with RTIs symptoms or respiratory distress. It can be supported if other characteristic signs are found during clinical examination, especially if the nasopharyngeal and oropharyngeal swab results are negative.